Plan estratégico exportador para la creación de una comercializadora de yuca dulce parafinada en la ciudad de Pereira, para su exportación a Estados Unidos. (2014)
The current project deals with the creation of a commercializing company of paraffined-sweet yucca. This study aims at looking for new international markets for the growing supply of this tuber in Risaralda state. In order to identify the target market, a series of studies aided to select the most appropriate country to export the agricultural product. This is why it is decided to export the product to Miami, USA, where there is a growing Latin American population that consumes the tuber as a traditional custom. Strategies regarding marketing, technical study, legal-administrative, environmental, and financial are proposed implementing a system that integrates efficiently all the aspects that foster competitiveness in the international market. For the sake of founding the commercializing company, it is required a budget of $35.696.461 as fixed investment and a working capital of $57.774.000, for a total investment of $93.470.461. Once the budget for the new proposed company is settled, the investment is evaluated in order to establish the viability from an investor perspective. For this, an Opportunity Interest Rate of 25% annually was established, which generated a cost benefit of over one and an Internal Rate of Return of 45.52%. Such indicators enable to conclude that the project is appealing as to execute it. Moreover, a stable targetmarket is suggested since the yucca is very desired by the Latin American population in the USA. This Nation also offers new commercial opportunities that are facilitated by the current Free Trade Agreement with the USA, which provides great opportunities of growth.